2015
DOI: 10.2196/resprot.4948
|View full text |Cite
|
Sign up to set email alerts
|

ProKaSaRe Study Protocol: A Prospective Multicenter Study of Pulmonary Rehabilitation of Patients With Sarcoidosis

Abstract: BackgroundAvailable data assessing the efficacy of pulmonary rehabilitation for patients with chronic sarcoidosis are scant; for Germany, there are none at all.ObjectiveTo gain information about the benefit of in-house pulmonary rehabilitation for patients with chronic sarcoidosis and for the health care system, we intend to collect data in a prospective multicenter “real-life” cohort trial.MethodsProKaSaRe (Prospektive Katamnesestudie Sarkoidose in der pneumologischen Rehabilitation) [Prospective Catamnesis S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Methods regarding sample size calculation and statistical procedures have been described previously [33]. …”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Methods regarding sample size calculation and statistical procedures have been described previously [33]. …”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Studies in IPF and Parkinson's disease have reported increased awareness of the benefits of home-based physical training, supervised by physical therapists online and/or by phone calls, in terms of reduction of burden of disease (muscle strength, exercise capacity, fatigue, mental status, and QoL), and the same benefits may be achieved in patients with sarcoidosis [6,79,80]. These findings could guide a feasibility study outlining 'best practice' in other chronic disorders, in which home-based supervised physical training programs are expected to improve QoL and reduce the burden of disease.…”
Section: Five-year Viewmentioning
confidence: 99%